1978
DOI: 10.1051/jphyscol:19786245
|View full text |Cite
|
Sign up to set email alerts
|

The Josephson Effect in Superconducting Constrictions : Microscopic Theory

Abstract: The d.c. Josephson effect in superconducting microbridges has been studied in terms of the microscopic theory of superconductivity. Current-phase relation, I (ϕ), and a critical current value, Ic(T), have been obtained and shown to be different from those quantities corresponding to the tunnel junction. These differences are most pronounced at low temperatures and for the pure constrictions : l≫a, l : being the electron mean free path and a : the radius of the orifice connecting two superconductors. In the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
50
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 0 publications
3
50
0
Order By: Relevance
“…where ∆ 0 is the superconducting energy gap, R N is the normal-state resistance of the contact, N is an integer (ϕ-dependence is identical with that of the classical ScS contact 20 ). The critical current of ScS atomic-size contact is quantized in consequence of quantization of the contact conductance R −1 N in units of G 0 = 2e 2 /h, that was observed experimentally 18 .…”
Section: Model and Numerical Analysismentioning
confidence: 99%
“…where ∆ 0 is the superconducting energy gap, R N is the normal-state resistance of the contact, N is an integer (ϕ-dependence is identical with that of the classical ScS contact 20 ). The critical current of ScS atomic-size contact is quantized in consequence of quantization of the contact conductance R −1 N in units of G 0 = 2e 2 /h, that was observed experimentally 18 .…”
Section: Model and Numerical Analysismentioning
confidence: 99%
“…In Ref. 7 it was shown that under assumption of small transparency of the tunnel barrier the wave function (and thus the current-voltage characteristics) can be found analytically for an arbitrary size of the tunnel area. The results in [6] for the conductance of the tunnel point contact were generalized to an arbitrary Fermi surface for the charge carriers in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…6 it was proposed to introduce in the theory of STM the model by Kulik et al [7]. In this model a three-dimensional STM tip is replaced by an inhomogeneous barrier in an otherwise nonconducting interface that separates the two conductors.…”
Section: Introductionmentioning
confidence: 99%
“…As a special case the authors of Ref. [17] considered a system of several orifices with different radii. The characteristic radius of the region through which the electrons tunnel from the STM tip into the sample has sub-atomic size (a ≃ 0.1Å) while the Fermi wave vector is k F ≃ 1Å −1 .…”
mentioning
confidence: 99%
“…The x axis is directed along the the line connecting the contacts. For the potential barrier in the plane z = 0 we use the function [17] U…”
mentioning
confidence: 99%